PENINGKATAN PRODUKTIVITAS PEMANENAN KAYU DI HUTAN ALAM MELALUI KESESUAIAN JUMLAH PEKERJA - Sona Suhartana; Yuniawati Yuniawati (Jurnal Hutan Tropis, 2020)
Timber harvesting has a significent role for timber production. In natural forest, the timber production may be increased in line with the efectiveness of forest harvesting. The number of worker in harvesting many contribute to improve natural forest harvesting. Research conducted on forest concession in north borneo the primary and secondary date the direct information based in measurement of log volume and the member of working hours in every activity step of harvesting. While the secondary information derived from the quisionare delivered to field manager apply multiple regressing is used to analysa the relation amongs member of worker used, produktivity in harvesting and production cost. the research finding showed that 1) the number of worker in following activities of cutting, skidding handling and log delivering are about 2, 9, 3 and 9 consecutively; 2) the average of productivity and harvesting cost for the activities of cutting, skidding handling and log delivery are about 38.308 m3/hour, 15.070 m/hour, 67.5 m3/hour, 8.33 m3/hour, while the cost arising for the activities are Rp13.897,44/m3, Rp.48.883,45/m3, Rp. 11.765,6/m3  and Rp. 74.039/m ; 3) the more harvesting workers are not directly increase the logging productivity. it many need some trainings to improved their capabilities; 4) the regression model among the member of worker and productivity of harvesting and production cost is Y=15,346 + 0,326 X1  +3,685X2